Collecting yam (Dioscorea spp.) and sweet potato (Ipomoea batatas) germplasm in traditional agriculture amall-holdigs in the Vale do Ribeira, Sao Paulo, Brazil - Andrade Breáan, E.=700 1 Veaáey, E.A.; Peroni, N.; Perez Felipim, A.; Pacheco dos Santos, K.M.
(Es, En, Fr)
ilus., 13 ref.
Keywords: DIOSCOREA; IPOMOEA BATATAS; GERMOPLASMA; AGRICULTURA TRADICIONAL; BRASIL; BATATA; ÑAME